Perancangan Meja Kopi Minimalis dari Limbah Triplek dan HPL yang Berkelanjutan - Shoka Muhammad Mufrikhun; Dwi Agus Susila; Sutarya Sutarya (Lembaga Pengembangan Kinerja Dosen, 2026)
Furniture is an item needed to complete the needs at home or residence, furniture helps the process of household chores become easier, as a place of storage, and creates comfort for its occupants. In this increasingly environmentally conscious era, product design is here to integrate the principles of sustainability. One of them is waste from industrial HPL (high pressure laminate) which is often thrown away without being utilized, Plywood waste and High Pressure Laminate (HPL) are by-products of the furniture industry that hold potential for reuse through sustainable design practices. This study aims to design a coffee table using plywood and HPL waste by applying the Design Thinking method, which includes the stages of empathize, define, ideate, prototype, and test. This method enables user needs analysis, idea exploration, and iterative prototype development. The results indicate that waste materials can be transformed into a coffee table that is strong, aesthetically appealing, and functional. The use of HPL enhances surface durability and visual value, while the plywood structure can be reinforced through simple joinery systems. The final product meets ergonomic, stability, and aesthetic criteria. In conclusion, Design Thinking is effective in transforming waste materials into high-value furniture and supports sustainable design practices